2018
DOI: 10.1007/s11357-018-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing long-term neuroinflammatory responses to encephalopathy using MRI approaches in a rat endotoxemia model

Abstract: Sepsis-associated encephalopathy (SAE) induces neuroinflammation, which is associated with cognitive impairment (CI). CI is also correlated with aging. We used contrast-enhanced magnetic resonance imaging (MRI), perfusion MRI, and MR spectroscopy to assess long-term alterations in BBB permeability, microvascularity, and metabolism, respectively, in a rat lipopolysaccharide-induced SAE model. Free radical-targeted molecular MRI was used to detect brain radical levels at 24 h and 1 week post-LPS injection. CE-MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 51 publications
2
41
0
Order By: Relevance
“…Up to now, IST has been applied in a variety of in-vitro and in-vivo studies, including animal disease models, in order to elucidate the impact of radical formation under physiological and pathological conditions. 451,464,[470][471][472] Instrumentation for ESR spectroscopy.-ESR spectrometers used in research and in clinical applications are rather expensive and complex instruments requiring experienced personnel for operation and evaluation of experiments. Currently, high-performance and automatized desktop ESR spectrometers become available, which can be operated following validated protocols for monitoring radicals in systems of living cells.…”
Section: Applications Of Spin Traps and Spin Probes-h 2 Omentioning
confidence: 99%
“…Up to now, IST has been applied in a variety of in-vitro and in-vivo studies, including animal disease models, in order to elucidate the impact of radical formation under physiological and pathological conditions. 451,464,[470][471][472] Instrumentation for ESR spectroscopy.-ESR spectrometers used in research and in clinical applications are rather expensive and complex instruments requiring experienced personnel for operation and evaluation of experiments. Currently, high-performance and automatized desktop ESR spectrometers become available, which can be operated following validated protocols for monitoring radicals in systems of living cells.…”
Section: Applications Of Spin Traps and Spin Probes-h 2 Omentioning
confidence: 99%
“…Our group has previously characterized an experimental LPS endotoxemia‐induced rat model of sepsis as resulting in secondary neuroinflammation and, based on evidence for delayed parenchymal enhancement on contrast‐enhanced MRI, of associated BBB disruption . Using this LPS‐induced model, we herein report greater deposition of Gd in the brain in LPS‐treated rats than in control animals throughout the interval of observation (to 6 weeks following GBCA administration).…”
Section: Discussionmentioning
confidence: 70%
“…It is possible that some degree of acute renal injury in the LPS‐treated rats during the first 24 hours after contrast injection could have resulted in higher GBCA levels in the blood and delivery to the brain, which may have normalized by 24 hours. Additionally, we have reported that brain perfusion is increased during the first 24 hours in LPS‐treated rats, which could also result in increased delivery of GBCA to the brain . Regardless of the specific and possibly multifactorial mechanism of increased Gd deposition in the brains of LPS‐treated rats, substantial deposition of Gd also occurs even in control rats for sustained intervals following injection of linear GBCA.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations